Enumeration of Fetal Red Blood Cells, Hemoglobin‐Specific RBC Cells, and F Reticulocytes in Human Blood. Issue 1 (26th June 2019) - Davis, Bruce H.
Abstract: Recent advances in analytical cytometry have improved diagnostic tools for the study of erythropoiesis in anemic patients and resolution of differential diagnosis in diseases of the erythron. This article presents three applications of red blood cell (RBC) analysis—quantitation of fetal red cells, F‐cell enumeration, and F‐reticulocyte analysis—which improve diagnostic precision, sensitivity, and specificity, and provide better laboratory indicators of therapeutic efficacy in a variety of hematologic and obstetric disorders. Such advances also include the measurement and quantitation of RBC hemoglobins and their relative ribonucleic acid levels. These advances not only promise to improve diagnostic accuracy and laboratory precision over techniques such as the traditional manual reticulocyte counting method and the Kleihauer‐Betke stain method for evaluating fetomaternal hemorrhage (FMH), but also serve as tools for newer assays of anemia diagnosis and improved clinical outcomes. In addition to the primary methods, supporting techniques for preparing spiked controls, automating data analysis, setting up a fetal hemoglobin acquisition protocol, and assaying reticulocytes using thiazole orange are also presented. © 2019 by John Wiley & Sons, Inc.